The influence of local governance on agricultural advisory services in Tajikistan - Andreas Mandler (Leibniz Institute of Agricultural Development in Central and Eastern Europe (IAMO), 2010)
The present article investigates the influence of local governance on agricultural advisory services in Tajikistan. The Central Asian Republic of Tajikistan is an agricultural country that has been described as a hybrid state, where local governance tends to be dominated by a few powerful actors. Local governance processes do have a strong influence on the agriculture practise and on the exchange of the knowledge. Agricultural advisory services claim various effects in the country. Especially in regions that are dominated by monocultures, advisory services have limited success. Therefore the present article assumes that the nexus of knowledge and innovation in Tajik agriculture is largely dependent on the decision-making of local governance processes. The article outlines the important role of local governance for distribution and use of knowledge in rural areas and emphasizes the context of agricultural advisory services in Tajikistan.
Keywords: 330; Tajikistan; Agriculture; Advisory service; Local governance; Elites